AGILE GOVERNANCE AS A STRATEGIC PARADIGM FOR PUBLIC SERVICE DIGITAL TRANSFORMATION: A SYSTEMATIC LITERATURE REVIEW - Yeti Rohayati (GoAcademica Research dan Publishing, 2023)
The rapid development of digital technologies has transformed the delivery of public services and increased the need for governance models that are adaptive, responsive, and citizen-cantered. Agile governance has emerged as a promising approach to addressing the limitations of traditional bureaucratic structures in supporting digital transformation initiatives. This study aims to systematically analyse the application of agile governance in the digital transformation of public services, identify critical success factors and implementation barriers, and examine its implications for public sector innovation and service performance. The research employs a Systematic Literature Review (SLR) approach using the PRISMA framework to identify, screen, evaluate, and synthesize relevant peer-reviewed articles published between 2013 and 2023. Data were collected from reputable academic databases and analysed using thematic analysis to identify recurring themes, trends, and patterns in the literature. The findings reveal that agile governance significantly contributes to improving organizational adaptability, service responsiveness, innovation capacity, stakeholder collaboration, and institutional resilience. The review also identifies leadership commitment, digital competencies, organizational culture, stakeholder engagement, and supportive regulatory frameworks as critical success factors. However, challenges such as regulatory rigidity, resistance to change, resource constraints, and coordination issues continue to impede effective implementation. The novelty of this research lies in its integrated synthesis of agile governance literature within the context of public service digital transformation, demonstrating that agile governance should be understood not merely as a managerial technique but as a comprehensive governance paradigm that balances flexibility, innovation, collaboration, and accountability to achieve sustainable and citizen-cantered public service transformation.